Casino Industry in the Transition Economy of Georgia - Bolkvadze, Besik (European Journal of Economics and Business Studies, 2022)
One of the most specific segments among the social-economic problems in the transition period of the market economy of Georgia is created by regulation of gambling (gambling business) and evaluation of its effect on a various part of society. Subsequently, the peculiar “triangle” is formed – “business – society – state” in which each of them has its interests, benefits and losses. One of the leading gambling businesses in the country is formed by the casino industry.The work deals with analysis and discussion of the role of casino industry and its importance in gambling business, objective and subjective factors of increase and development of the segment, effects of its positive and negative influence on stakeholders, fiscal determinants, financial-economic and social-economic problems of the sub-sector, proper recommendations have been developed on the basis of the theoretical and empirical analysis and conclusions.